2018
DOI: 10.3390/molecules23020256
|View full text |Cite
|
Sign up to set email alerts
|

Nigella damascena L. Essential Oil—A Valuable Source of β-Elemene for Antimicrobial Testing

Abstract: The most commonly used plant source of β-elemene is Curcuma wenyujin Y. H. Chen & C. Ling (syn. of Curcuma aromatic Salisb.) with its content in supercritical CO2 extract up to 27.83%. However, the other rich source of this compound is Nigella damascena L. essential oil, in which β-elemene accounts for 47%. In this work, the effective protocol for preparative isolation of β-elemene from a new source—N. damascena essential oil—using high performance counter-current chromatography HPCCC was elaborated. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 32 publications
2
16
0
1
Order By: Relevance
“…In our search for new compounds of possible pharmaceutical interest, we previously carried out chemical investigations of male and female S. molle (L.) fresh leaf extracts and they were shown to be mainly composed of sesquiterpene hydrocarbons and monoterpene hydrocarbons [33]. We found the presence of molecules-such as elemol, β-elemene, β-caryophyllene, germacrene D, bicyclogermacrene, spathulenol, α-eudesmol, β-eudesmol, γ-eudesmol, isocalamendiol, sabinene and n-hexadecanoic acid-that could be related to possible antibacterial, antiviral and antifungal activities, as already reported in literature [34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionsupporting
confidence: 80%
“…In our search for new compounds of possible pharmaceutical interest, we previously carried out chemical investigations of male and female S. molle (L.) fresh leaf extracts and they were shown to be mainly composed of sesquiterpene hydrocarbons and monoterpene hydrocarbons [33]. We found the presence of molecules-such as elemol, β-elemene, β-caryophyllene, germacrene D, bicyclogermacrene, spathulenol, α-eudesmol, β-eudesmol, γ-eudesmol, isocalamendiol, sabinene and n-hexadecanoic acid-that could be related to possible antibacterial, antiviral and antifungal activities, as already reported in literature [34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionsupporting
confidence: 80%
“…Currently, Curcuma wenyujin , belonging to the Zingiberaceae family, is the plant most applied to the extraction of β-elemene [ 44 ]. Our results suggest that jabuticabas, mainly the ‘Esalq’ and ‘Escarlate’ species, are a natural source of this compound, which displays the potential to be used as a raw material for its extraction, as reported for Nigella damascena [ 45 ].…”
Section: Resultsmentioning
confidence: 63%
“…127 Other EOs showing efficacy in studies against MDR-and XDR-TB are Myrtus communis L. 128 and Nigella damascena. 129 Our study showed LVO is a promising antimicrobial extract, which can be used in combinatory therapy and may possibly be effective in reviving the efficacy of carbapenem and other antibiotics against other resistant bacteria. We propose the overall mode of action of LVO: disrupting the bacterial membrane via oxidative stress.…”
Section: Mdr and Xdr Tuberculosismentioning
confidence: 67%